Surviving and thriving in thrombosis research during a global pandemic: Experiences of a vascular scientist diagnosed with COVID-19 - Addie B. Spier; Colin E. Evans (Thrombosis Update, 2021)
The 2019–2020 COVID-19 outbreak resulted in widespread suffering along with major changes in the ways that researchers carry out their work. This article profiles the experiences of an early-career investigator in thrombosis research who worked through the COVID-19 pandemic and a COVID-19 diagnosis. The aims of this article are to normalize concern regarding COVID-19 in the research community, to provide a perspective on maintaining productivity during stay-at-home periods, and to discuss how the COVID-19 pandemic might alter common research practices in the future. While the COVID-19 outbreak was clearly disruptive and debilitating on a global level, some research practices that were heavily employed during the pandemic may continue to be utilized in scientific research for many years to come.